UPAYA PENINGKATAN KESADARAN REMAJA TENTANG PERSIAPAN MENJALANI PERNIKAHAN MELALUI SEMINAR KESEHATAN REPRODUKSI REMAJA - Rany Ekawati; Ema Novita Deniati; Windi Chusniah Rahmawati; Anisa Noor Cahyani; Azza Rizqia Vatrisa (ABDI MAKARTI, 2023)
Adolescence is an important period in life. In adolescence, it is often directed at understanding the importance of maintaining and caring for reproductive health. One case of adolescent problems that are rife is early marriage. Cases of early teenage marriages show an increasing number of cases. Efforts that can be made to suppress cases of early marriage are by holding activities that aim to increase youth awareness about marriage. Education in preparation for marriage by holding outreach and discussions packaged in seminars. This seminar activity is carried out online using zoom clouds meetings. The material discussed by the two speakers was on the topic of preparing for marriage. In addition, media was created to support adolescent understanding, namely by making an E-book entitled "All About Before Married". The results of the activities that have been carried out, most of the participants gave a positive response, seen from the enthusiasm in carrying out the wedding preparation seminar.